Ortaçağ İslam Dünyasında Dokuma Sanayi - Bakır, Abdülhalik (Türk Tarih Kurumu [EN], 2000)
Dokuma sanayi, insanlık tarihi kadar eski bir sanayi dalıdır. Zira giyim-kuşam ihtiyacı insanların hayatlarını sağlıklı bir biçimde sürdürmeleri için gerekli olan yeme, giyinme ve barınma ihtiyaçlarından birini teşkil etmektedir. Arkeolojik çalışmalar, dokuma sanayinin çok eski devirlere kadar uzandığını ortaya koymuştur. Bunlardan birisi de sanayi dalında çalışan birçok dokuma işçisinin adlarını ve bu işçilerin meslekleri ile ilgili bilgileri kapsayan Asurlular dönemine ait tabletlerde Sargon devrine dair Akad dili ile yazılmış kitabelerdir. Bu tablet ve kitabelerde dokuma sanayinde çalışan işçilerle, Asur kraliyet ailesi fertleri arasındaki ilişkiler hakkında bilgilere rastlandığı gibi, o devirde faaliyet gösteren dokuma atölyeleri ve özel dokuma fabrikaları ile ilgili geniş malumat verilmektedir.

Clothing has been known since antiquity as one of the basic necessities of human life. At first, humankind made clothing from sheep's wool and goat and camel hair and eventually from substances, like flax, silk fiber and cotton, and significant progress was marked. Simple clothing was characteristic of the era of the Prophet Muhammed and the first four caliphs while, in subsequent periods, demand arose for garments of fine woven fabric and ornamentation, to which may be attributed the reason for the growth in importance of the weaving sector. Throughout the medieval period, the weaving industry exhibited constant growth and in time became not only an active sector of employment, but it also gave rise to the textile trade in a number of cities. As a result of all these developments, Turkestan, Asia Minor, Persia, Azerbaijan, Armenia, Iraq, Syria, Yemen, Egypt and Andalusia each became known for excellence in the production of certain precious and ornamented fabrics peculiar to their locale. Carpet weaving, which formed the textile sector without rival in the Middle East and which, in the medieval period, underwent development particularly in Turkestan, Asia Minor, Persia, Azerbaijan, Iraq, Egypt and Andalus-places where fine carpets were woven in thousands of ateliers and exported. In addition, we should also recall that the manufacture of woven rush mats and rope advanced by great strides in the Islamic world. Those countries lacking competitors in this sphere in the medieval period were Lebanon, Palestine, Persia, Egypt, and India. As for the dying industry, the various fabrics and carpets manufactured in the weaver's ateliers in the medieval period were dyed with natural dyes obtained from plants; but, at the same time, certain mineral and animal dyes were also employed. Control over subterfuges executed in all branches of the textile industry was in the hands of the market inspectors appointed by the government, and any weavers who displayed shoddy practices were at once issued warnings, fines, revocations of permission to engage in trade and public display of their defective goods.
Textile Manufacturing in the Medieval Islamic World
Keywords: Archaeology; Arkeoloji